Moscow's lessons from the 1982 Lebanon air war - Lambeth, Benjamin S.; Project Air Force (U.S.). National Security Strategies Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 1984)
This report reviews Soviet impressions of Israeli air operations during the 1982 Lebanon war. It evaluates a 1983 article published in Soviet Air Force Monthly (whose audience includes Soviet aircrews), that assesses the implications of the Israeli-Syrian air battles. For Western audiences, the article provides insights into how the Soviets have interpreted the Beka'a Valley experience. It appears that the Soviets have either deliberately misrepresented Israel's air combat results to their own pilots or else failed to comprehend the tactical lessons suggested by Israeli combat performance.
"Project Air Force"--Cover.
"September 1984."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Aeronautics, Military -- Soviet Union; Air warfare; Lebanon -- History -- Israeli intervention, 1982-1984 -- Aerial operations